Long-term Field Measurements of Moisture in Wooden Walls with Different Types of Facades: Focus on Driving Rain Tightness. (November 2015) - Olsson, Lars
Abstract: Moisture damage has been found in houses having well-insulated, rendered (ETICS) wooden stud walls. However, there is no well documented experience from subsequent long-term monitoring of moisture conditions in such walls or indeed in other walls, for instance in ventilated facades. Long-term measurements show rain leakage within the exterior walls in five of a total of seven buildings during 2009–2011 and extended measurements until 2015 show continued leakages. We have not seen any difference in the number of leakage occasions when we compare ventilated and unventilated facades. It is also clear that the detailed solutions are not verified with regard to driving rain.